Good Intentions Are Not Enough: Centering Equity in School Discipline Reform. Issue 2 (3rd July 2021) - Gregory, Anne; Osher, David; Bear, George G.; Jagers, Robert J.; Sprague, Jeffrey R.
Abstract: Exclusionary discipline is commonly employed in U. S. schools and disproportionately affects students of color. This article describes current approaches to discipline and contextualizes these approaches historically with particular attention to racial dynamics and violence. We identify the harmful effects of exclusionary discipline and describe efforts to move schools away from exclusionary approaches through school-wide positive behavioral intervention supports, social emotional–learning, and restorative practices. We identify limitations of current discipline reform efforts that are hampering progress toward equitable schooling. We explicate the need for integrative and comprehensive culturally responsive approaches to positive student development that are equity oriented and identify implementation challenges and tools for addressing these challenges. Impact Statement The paper guides practitioners in evaluating whether their own school discipline reform efforts have promise or pitfalls for substantially reducing disparities. Practitioners are urged to consider the degree to which their discipline reform efforts may (a) ignore institutional oppression, (b) profess cultural neutrality, (c) neglect to integrate robust social, emotional, and behavioral supports, and (d) fail to include equitable access to academic rigor and challenge. The paper then offers practitioners directions for developing integrative, equity-oriented, and culturally responsive approaches to change.